The New Paigrave Dictionary of Money and Finance - Campbell, John Y. (Journal of Economic Literature, 2016)
The New Palgrave Dictionary of Money and Finance is a successor to the 1987 work The New Palgrave: A Dictionary of Economics. Both dictionaries claim descent from Palgrave's Dictionary of Political Economy, published as a summary of the state of economics during the 1890s. The same team of three editors is responsible for both New Palgrave dictionaries,1 and there are many similarities in approach. Indeed, about 20 percent of the essays in the New Palgrave Money and Finance are reprinted from the New Palgrave Economics (and ten essays are reprinted from the original Palgrave). There are also some obvious differences between the two New Palgrave dictionaries. The New Palgrave Economics had a much broader scope, aiming to cover all of modern economics. It was considerably larger than the New Palgrave Money and Finance, with four volumes rather than three, 3500 pages rather than 2500, and almost 2000 essays rather than 1000 or so. The New Palgrave Economics included biographical essays, which took up about a third of the work; the New Palgrave Money and Finance has no biography but includes many short definitions of technical terms. Last but not least, the New Palgrave Economics omitted empirical topics to concentrate on economic theory and history of economic thought, while the New Palgrave Money and Finance covers much empirical material.